The role of oestrogen and oestrogen-calcium axis in endometrial carcinoma - Jingyi Zhou; Jianliu Wang; Xuerun Liu (Gynecology and Obstetrics Clinical Medicine)
Unopposed oestrogen is recognised as an inducer of endometrial cancer. Over the past 50 years, the effects of oestrogen on the endometrium and endometrial cancer have been a hot topic in the field of gynaecological oncology. In recent years, a series of studies by our team revealed that the non-genomic transcriptional effects of oestrogen can influence the progression of endometrial carcinoma by regulating calcium ions, suggesting that inhibiting calcium ion channel proteins could serve as an adjuvant therapy for endometrial cancer. In this review, we retrospectively summarise the sources of oestrogen in vivo, the effects of oestrogens on the uterus and endometrium, oestrogen signalling and the clinical application of oestrogen-related compounds, emphasising the significant role of oestrogen–calcium axis inhibition in adjuvant therapy for endometrial cancer.